2013
DOI: 10.7314/apjcp.2013.14.5.3299
|View full text |Cite
|
Sign up to set email alerts
|

Global Adult Tobacco Survey (GATS): A Case for Change in Definition, Analysis and Interpretation of "Cigarettes" and "Cigarettes Per Day" in Completed and Future Surveys

Abstract: Background: The Global Adult Tobacco Survey has 15 key indicators, cigarettes smoked per day (CPD) among daily smokers being one of them. The first wave of GATS in 14 countries indicated that mean CPD use is higher in women than men in India only, which is contrary to the current understanding of tobacco use globally. This study was undertaken to understand the unusual findings for mean CPD use in the GATS-India survey. Materials and Methods: Items B06a and B06b of the GATS India survey questionnaire that coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…[2] The Global Adult Tobacco Survey (GATS) in 2010 revealed that 47.9% of males and 20.3% of females, constituting 34.6% of the adult population, used tobacco in one or the other form in India. [34] Social and cultural acceptance among youth is one of the reason for higher prevalence of tobacco consumption in India.…”
Section: Introductionmentioning
confidence: 99%
“…[2] The Global Adult Tobacco Survey (GATS) in 2010 revealed that 47.9% of males and 20.3% of females, constituting 34.6% of the adult population, used tobacco in one or the other form in India. [34] Social and cultural acceptance among youth is one of the reason for higher prevalence of tobacco consumption in India.…”
Section: Introductionmentioning
confidence: 99%
“…Further information about number of cigarettes is likely to be under reported and inaccurate as smokers tend to round off to five,10 etc. (known as ‘heaping’) and do not report exact number of sticks smoked during the previous 24 h [ 34 ]. We examined a change in ten countries having data from at least five years intervals and the most recent survey done was during 2015 or later.…”
Section: Discussionmentioning
confidence: 99%
“…Further information about number of cigarettes is likely to be under reported and inaccurate as smokers tend to round off to five,10 etc. (known as 'heaping') and do not report exact number of sticks smoked during the previous 24 hours [33]. We examined a change in ten countries that had at least five years interval and most recent survey done was during 2015 or later.…”
Section: Discussionmentioning
confidence: 99%